Fine structures and their impacts on the characteristic Raman spectra of molten binary alkali tungstates. (13th June 2021) - Wang, Jian; Wang, Min; You, Jinglin; Lu, Liming; Wan, Songming; Wu, Yongquan; Zheng, Shaobo
Abstract: Comparing with the crystalline tungstate compounds, little work has been carried out and reported on the relation among the microstructure, W–O bond lengths, and characteristic Raman‐active vibration wavenumber of the molten tungstates, which allows us to diagnose and determine the structure of unknown clusters existing in and further predict the physicochemical properties of molten binary alkali tungstates. Raman spectra of an ensemble of eight model clusters were simulated in the present work by density functional theory (DFT) to establish the effect of the fine structures and W–O nb (non‐bridging oxygen) bond lengths of W–O complexes on the characteristic wavenumber of W–O nb Raman‐active vibration modes of the molten tungstates. Results show that the characteristic wavenumbers of the symmetric stretching vibration modes of W–O nb bonds increase almost linearly with the decreasing bond length. The characteristic wavenumbers of W–O nb symmetric stretching vibration modes generally follow [WO4 ] 2−  > [WO5 ] 4−  > [WO6 ] 6− present in the melt simultaneously. The characteristic wavenumbers were also found to increase with the number of bridging oxygen for the same W–O complex. In situ Raman spectra of molten A2 Wn O3n + 1 (A = Li, Na, K; n  = 1, 2, 3) were then measured in order to verify the correlation observed among the microstructure, W–O bond lengths, and characteristic Raman‐active vibration mode wavenumbers. The correlation was successfully applied to deconvolute the in situ Raman spectrum of the molten Na2 W3 O10 . Abstract : The correlation between W–O nb average bond length and characteristic wavenumber of W–O nb stretching vibration of fine structures in A2 O–WO3 (A = Li, Na, and K) binary melts was obtained. The characteristic wavenumber of W–O nb symmetric stretching vibration mode in melt generally follows ν ( Q i ) >  ν ( P i ) >  ν ( H i ). The characteristic wavenumber of W–O nb symmetric stretching vibration mode will increase with the increasing number of bridging oxygen, namely, i within the same W–O complex.